Exploring variation of length of haul and associated freight transport emission of Indian establishments: A survival analysis approach - Mishra N.B.; Mohapatra S.S.; Pani A.; Sahu P.K. (My University, 2025)
Rise in length of haul (LOH) of business establishments and the associated greenhouse gas (GHG) emissions are a major concern for planners and policymakers, require extensive investigation. This paper quantifies various factors like business age, gross floor area, employment, the build environment variable on LOH, and associated GHG emission using EBFS data. Survival analysis has been utilized for the analysis. The aggregated LOH model provides a comparative analysis of LOH across different industry sectors and demonstrate that gross floor area, business age, and employment are positively associated with LOH. Subsequently, disaggregated LOH models are reveal the influencing parameter of LOH of a particular industry category. Lastly, GHG models show the influence of fleet ownership level on GHG emissions across different industry sectors. The outcomes will be beneficial for planners and policymakers to develop industry-specific regulations on land use, employment restructuring, and subsidies for owning different types of commercial vehicles. © 2023 Elsevier Ltd